2002
DOI: 10.1097/00044067-200211000-00003
|View full text |Cite
|
Sign up to set email alerts
|

Education for Genetics and Nursing Practice

Abstract: Genetic factors influence the risk for disease, selection of treatments, and overall health of persons throughout the life span. Nurses in critical care practice participate in assessing genetic risks for disease, implementing treatments, educating people about genetic aspects of health and disease, supporting the client's abilities to cope with the information, and assisting the individual and family to make health-related decisions involving genetic information. Opportunities for critical care nurses to beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 16 publications
1
7
0
Order By: Relevance
“…This result was consistent with previous studies that indicated that once information is collected, it might be the confirmation of the diagnosis of the family that is necessary whereby nurses and midwives should teach the client and his/her family about risk, diagnosis, inheritance pattern and testing, in addition to providing emotional support (Hamamy et al. 2007; Williams 2002). In order to effectively carry out the nursing role, Jenkins et al.…”
Section: Discussionsupporting
confidence: 92%
“…This result was consistent with previous studies that indicated that once information is collected, it might be the confirmation of the diagnosis of the family that is necessary whereby nurses and midwives should teach the client and his/her family about risk, diagnosis, inheritance pattern and testing, in addition to providing emotional support (Hamamy et al. 2007; Williams 2002). In order to effectively carry out the nursing role, Jenkins et al.…”
Section: Discussionsupporting
confidence: 92%
“…A great deal of education remains to be done to improve medical genetics competency in the nursing community. Guidelines for the medical genetics education of nurses have been developed; however, medical genetics education is not included in curricula for all nurses throughout the United States (Williams, 2002). The failure to integrate medical genetics into nursing curricula is because of a lack of consensus among nursing educators on the importance of medical genetics in nursing curriculum, the feeling that there is insufficient time to teach additional medical genetics content, and the lack of trained faculty to teach medical genetics content (Anderson, 1996; Jenkins, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Formal genetics training prepares nurses to identify patients who are at risk of genetically‐based health problems, and promotes patient education and early intervention (Petska & Brown, 2004). Proponents assert that genetics expertise will allow nurses to better educate patients about the conditions that they currently suffer from and how this will impact their health (Williams & Cheek, 2002; Prows et al ., 2003). To this end, many members of the nursing community have advocated for clear, uniform guidelines to be put into place and adopted by genetic nursing education programs across the country (Williams & Cheek, 2002; Williams et al ., 2004; Dodson & Lewallen, 2011).…”
Section: Introductionmentioning
confidence: 99%